Profil hasil karya p5 siswa sekolah dasar di daerah pegunungan dan pesisir ditinjau dari perspektif ecological art - Lusiana Firdani; Karsono Karsono; Peduk Rintayati (Universitas Sebelas Maret, 2024)
P5 or the Pancasila Student Profile Strengthening Project is part of the Independent Curriculum. The issue of environmental damage gave rise to the term Ecological Art. Ecological Art refers to the sustainable use of natural resources through works of art. This study looked at works of art in mountainous and coastal elementary schools to obtain an overview of student and environmental interaction practices. The purpose of this study was to identify the profile of works of art by coastal and mountainous elementary school students from an Ecological Art perspective. This study used a qualitative research method. Qualitative research is based on events that actually happened. This method will answer problems or realities that occur in depth. Meanwhile, the approach used is a case study. A case study is one of the research approaches that focuses on exploring events in real life. Both schools in coastal and mountainous areas have implemented five aspects of Ecological Art in P5 learning. Aspects of Ecological Art include the use of natural materials in works of art, promoting sustainable environmental development, collaborative activities in works of art, utilising recycled materials, and realising environmental conservation messages. In general, the two schools have similarities in implementing P5 activities. The profile of P5 works of students at SD Negeri 1 Gondanglegi and SD Negeri 2 Kalijoyo have been integrated with aspects of Ecological Art. P5 activities and students' artwork in grade IV of SD Negeri 1 Gondanglegi and SD Negeri 2 Kalijoyo can be implemented well and meet the research indicators compiled by the researcher.